Material comparative analysis of crack-bridging degradation of SFRC structural beams under flexural fatigue loading. (11th July 2022) - Adel, Mohamed; Matsumoto, Koji; Ueda, Tamon; Nagai, Kohei
Highlights: Effects of several material parameters are investigated on the cyclic crack-bridging degradation of SFRC structural beams. The concrete strength, fracture energy level, steel-fiber geometry, and rebar reinforcement ratios of SFRC are studied. The steel fibers cyclic debonding inside the tensile stress zone is strongly affected by the fracture energy level. Crack-bridging degradation diagrams against maximum rebar strain could capture the effect of SFRC mechanical properties. Abstract: This study experimentally investigates the influence of several material parameters on steel fiber reinforced concrete (SFRC) structural beams and their crack-bridging degradation over constant and variable amplitudes of flexural cyclic loading. Crack-bridging stress is evaluated using inverse analysis and its degradation against maximum rebars strain is derived. Four series of SRFC beams are prepared and characterized with different concrete compressive strengths, hooked-end steel fiber shapes in two different volume fractions, and two longitudinal reinforcement ratios. The results reveal lower crack-bridging degradation rates, and associated longer fatigue life and higher residual capacity, for beams with higher concrete strength. Further, SFRC fracture energy is shown to have a significant effect on fatigue response, with higher fracture energy associated with lower rates of crack-bridging degradation. However, steel fibers with double hooks are shown to have a relatively insignificant effect on controlling crack-bridging degradation rates and the flexural cyclic responses of SFRC beams as compared to single hook fibers. Also demonstrated is that a lower longitudinal reinforcement ratio leads to higher rebar strain rates with no influence on crack-bridging stress. Crack-bridging degradation diagrams are proposed for SFRC beams that quantitatively capture several material parameters effects based on their mechanical properties over the fatigue life.